Does Employing Older Workers Affect Workplace Performance? - Alex Bryson; John Forth; Helen Gray; Lucy Stokes (Institute of Labor Economics (IZA), 2019)
Focusing on private sector workplaces in Britain, we investigate whether the employment of older workers has implications for workplace performance. We find no significant association between changes in the proportion of older workers employed and changes in workplace performance. We find some evidence that workplace labour productivity falls where the proportion of 'middle-aged' workers falls, either due to a rise in the proportion of older or younger workers, but this association does not carry through to financial performance. Overall, the findings suggest that any reluctance on the part of employers to employ greater numbers of older workers may be misplaced.
Keywords: J21; J23; J24; J63; L25; M51; 330; older workers; productivity; workplace employment relations survey